EFEKTIVITAS PENAMBAHAN ENZIM CAIRAN RUMEN DOMBA TERHADAP PENURUNAN SERAT KASAR BUNGKIL KELAPA SEBAGAI BAHAN BAKU PAKAN IKAN - Zuraida .; Dedi Jusadi; NurBambang Priyono Utomo (Jurnal Akuakultur Rawa Indonesia, 2013)
Experiments to evalueate the hydrolysis of crude fiber in coconut cake meal (CCM) by sheep rumen liquor enzymes for basic material fish diet. In Experiment I, the sheep rumen liquor enzymes were added into the CCM at concentration of either 0, 25, 50, 75, 100, or 125 ml/kg of CCM, and incubated for the period of 0, 12, and 24 hours, respectively. The result showed that sheep rumen liquor enzymes could effectively reduced the fiber content of CCM, while its glucose concentration increased. It was found that the application of sheep rumen liquor enzymes at a dose of 125 ml in 1 kg CCM at a period of 24 hours was the most effective treatment to reduce the crude fiber content in CCM. The crude fiber content in this treatment decreased from 13.76% to 6.98%. Keywords: coconut cake meal, sheep rumen liquor, and crude fiber